Finerenone in Diabetic-Kidney Disease, True Result Renal and Cardiovascular Outcome: A Meta-Analysis - Felicita Gracia; Arya Marganda Simanjuntak; Samira Amanda; Linda Ida Mustika; Juwanto; Ligat Pribadi Sembiring; Jazil Karimi; Sari Harahap; Rosmaliana (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Diabetic kidney disease (DKD) is a major complication of type 2 diabetes, increasing cardiovascular risk. Existing treatments leave significant residual progression risk. Finerenone, a novel nonsteroidal mineralocorticoid receptor antagonist, shows promise. This meta-analysis evaluates finerenone's effects on renal and cardiovascular outcomes in DKD. A Systematic Review and Meta-Analysis (PROSPERO CRD420251122382) followed PRISMA guidelines. PubMed, ScienceDirect, and Epistemonikos utilized and used keywords